Specific alleles at immune genes, rather than genome‐wide heterozygosity, are related to immunity and survival in the critically endangered Attwater's prairie‐chicken. Issue 19 (6th September 2016) - Bateson, Zachary W.; Hammerly, Susan C.; Johnson, Jeff A.; Morrow, Michael E.; Whittingham, Linda A.; Dunn, Peter O.
Abstract: The negative effects of inbreeding on fitness are serious concerns for populations of endangered species. Reduced fitness has been associated with lower genome‐wide heterozygosity and immune gene diversity in the wild; however, it is rare that both types of genetic measures are included in the same study. Thus, it is often unclear whether the variation in fitness is due to the general effects of inbreeding, immunity‐related genes or both. Here, we tested whether genome‐wide heterozygosity (20 990 SNPs) and diversity at nine immune genes were better predictors of two measures of fitness (immune response and survival) in the endangered Attwater's prairie‐chicken ( Tympanuchus cupido attwateri ). We found that postrelease survival of captive‐bred birds was related to alleles of the innate (Toll‐like receptors, TLRs) and adaptive (major histocompatibility complex, MHC) immune systems, but not to genome‐wide heterozygosity. Likewise, we found that the immune response at the time of release was related to TLR and MHC alleles, and not to genome‐wide heterozygosity. Overall, this study demonstrates that immune genes may serve as important genetic markers when monitoring fitness in inbred populations and that in some populations specific functional genes may be better predictors of fitness than genome‐wide heterozygosity.